2009
DOI: 10.1093/eurheartj/ehp156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary angioplasty and pre-hospital fibrinolysis in acute myocardial infarction (CAPTIM) trial: a 5-year follow-up

Abstract: The 5-year follow-up is consistent with the 30-day outcomes of the trial, showing similar mortality for primary percutaneous coronary intervention and a policy of pre-hospital lysis followed by transfer to an interventional center. In addition, for patients treated within 2 h of symptom onset, 5-year mortality was lower with pre-hospital lysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
21

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(122 citation statements)
references
References 14 publications
2
99
0
21
Order By: Relevance
“…The observation that the time required for primary PCI to be started was on average 4 hours longer than the time taken to initiate fibrinolytic therapy suggests that this type of reperfusion could be performed as an alternative reperfusion approach for cases when the expected time for transferring the patient for PCI is too long. The results of the CAPTIM (Comparison of Primary Angioplasty and Pre‐hospital Fibrinolysis in Acute Myocardial Infarction) study indicated that prehospital fibrinolysis, particularly in the first 2 hours after symptoms onset, can be more effective than transfer for primary PCI 20. In fact, 2 major registries—the Vienna STEMI Registry21 and the French Registry on Acute ST‐Elevation and Non‐ST‐elevation Myocardial Infarction (FAST‐MI) 201022—showed similar results for patients treated at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the time required for primary PCI to be started was on average 4 hours longer than the time taken to initiate fibrinolytic therapy suggests that this type of reperfusion could be performed as an alternative reperfusion approach for cases when the expected time for transferring the patient for PCI is too long. The results of the CAPTIM (Comparison of Primary Angioplasty and Pre‐hospital Fibrinolysis in Acute Myocardial Infarction) study indicated that prehospital fibrinolysis, particularly in the first 2 hours after symptoms onset, can be more effective than transfer for primary PCI 20. In fact, 2 major registries—the Vienna STEMI Registry21 and the French Registry on Acute ST‐Elevation and Non‐ST‐elevation Myocardial Infarction (FAST‐MI) 201022—showed similar results for patients treated at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-hospital full-dose fibrinolysis has been tested in the CAPTIM trial [81], using an emergency medical service (EMS) able to perform pre-hospital diagnosis and fibrinolysis, with equivalent outcome to primary PCI at 30 days and 5 years. Following pre-hospital fibrinolysis, the ambulance should S16 transport the patient to a 24 h a day/7 days a week PCI facility.…”
Section: Fibrinolysismentioning
confidence: 99%
“…Despite the study' sample size, a high percentage of No Reflow was identified in a reference hospital because patients arrived after the first two hours of symptom evolution, which was shown to be beneficial for any of the reperfusion strategies in the CAPTIM study [16]. The No Reflow phenomenon has been associated with major cardiovascular events, including clinical complications such as hypotension that does not reflect myocardial damage and electrical complications such as bradycardia, ventricular arrhythmias, and complete atrioventricular block, which are secondary to cell damage and membrane instability [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The No Reflow phenomenon has been associated with major cardiovascular events, including clinical complications such as hypotension that does not reflect myocardial damage and electrical complications such as bradycardia, ventricular arrhythmias, and complete atrioventricular block, which are secondary to cell damage and membrane instability [16,17]. The ejection fraction was significantly lower in group II, as demonstrated in a previous work by our research group, in which IL6 levels in serum were determined during the first 24 hours, which indicates that there is microvascular and functional myocardium damage, reducing the rate of left ventricular mobility [15,17].…”
Section: Discussionmentioning
confidence: 99%